PENGHITUNGAN LUAS PERAIRAN PEDALAMAN DAN LUAS PENGELOLAAN WILAYAH LAUT DAERAH (STUDI KASUS : PROVINSI GORONTALO DAN SULAWESI UTARA) - J. P. Nainggolan, Trison
The Republic of Indonesia is an archipelagic country with an area of water that dominates its land area. The large potential of the territorial waters owned by Indonesia must then be balanced with the large amount of responsibility in its management. One of them is the management of the provincial sea area which has been regulated through Law Number 23 of 2014 and Ministerial Regulation of Home Affairs Number 141 of 2017. One example of its application is through the determination of the management area of the marine area of Gorontalo Province and North Sulawesi Province which must be preceded by the determination of boundaries. The area between the two provinces, then proceed with determining the management area of the sea area of the province as far as 12 nautical miles from the coastline in accordance with the stipulated articles and paragraphs. This is useful for determining the area of provincial marine management which can be used as a factor in determining the General Allocation Fund from the central government. Similar to the determination of regional marine management areas, the determination of inland water areas is also part of the management of territorial sea areas and has been regulated in the International Law of the Sea, UNCLOS III (1973-1982), which technically states that it is necessary to determine the closing line (at rivers, bays and port) to determine the inland water area. The data used in this research is Topographic Map of Indonesia, where the assumption is made that the coastline used is the mean sea level. The method used in determining the area of the provincial marine area management is the buffer method and the determination of the median line is done by the Thiessen polygon method. Based on the process that has been carried out, it is found that the management area of the marine area of Gorontalo Province is 9,316.3 Km2 and North Sulawesi Province is 48,353.1 Km2. Then the results of the calculation of the area of inland waters in Gorontalo Province is 135.6967 Km2 and the area of Inland Waters in North Sulawesi Province is 213.5789 Km2.